Evaluation of Academic Information Systems in Realizing Good University Governance - Fatkuroji; Wahyudi; Lateh, Fadleena; Fadhilah, Anna Rizqi (Munaddhomah: Jurnal Manajemen Pendidikan Islam, 2025)
This study aims to measure the influence of Academic Information System (AIS) on Good University Governance (GUG) at UIN Walisongo Semarang. This study using a quantitative method with data collection through a survey involving academic staff, students, and PTIPD management. The research instrument is a questionnaire designed to measure transparency, accountability, and participation. The data obtained were analyzed using linear regression to evaluate the contribution of the AIS to each aspect of GUG. The results showed that the AIS contributed 0.832 to transparency, 0.862 to accountability, and 0.884 to participation. Optimal implementation of the AIS has been proven to be able to significantly improve these three aspects, which ultimately strengthens the principles of Good University Governance. Increased transparency through the AIS allows easier and faster access to academic information, while better accountability supports more effective supervision. In addition, increased participation allows for broader involvement of all stakeholders in the decision-making process. These findings confirm that the AIS plays a direct role in improving the quality of university governance more effectively. This study also provides an important contribution to the literature on university governance by emphasizing the role of information technology in enhancing transparancy, accountability, and participation. The practical implication of this study is the importance of developing more efficient SIA implementation strategies to support good university governance and improve overall academic performance.